DESIGNING OF TURN-OUT CORE BOXES WITH LOOSE SIDES - V. A. Skvortsov; A. A. Skvortsov (Литьë и металлургия)
Designs of the turn-out core boxes with loose sides are given. Standard designs of elements of the turn-out core boxes with loose sides depending on their sizes are given. Tabular data of the sizes and fasteners of these elements of turn-out core with loose sides according to the existing state standard specifications are provided. Content of the article allows to reduce considerably duration of designing of the turn-out core boxes with loose sides in preparation of new technological processes of cast details production.